Natrium Silikat Sebagai Inhibitor Korosi Pada Pipa Penyalur Minyak Bumi Jenis Carbon Steel - Saputra, Andika; Hakim, Arief Rakhman; Hamdani, M Zulva; Alamsyah, Asfitrah; Amalia, Yasmina (Fakultas Teknik UMSU, 2022)
Corrosion in the pipeline can cause leaks so crude oil directly pollutes the ocean ecosystem. Therefore, proper preventive methods are needed, such as using inhibitors. So far, the corrosion inhibitors used in the petroleum industry are of an inorganic type which can cause new problems such as toxicity to the environment and endanger human health. This paper describes an organic inhibitor based on sodium silicate obtained from rice husks through a synthetic method. The source of this inhibitor is very abundant in nature and the silica content is relatively high, around 86.90-93.70%. This inhibitor from rice husk, apart from having a good ability to reduce corrosion rates, also has the potential to be produced commercially.